Nietzsche : a novel - Krell, David Farrell (SUNY series in contemporary continental philosophy., 1996)
A fictionalized biography of the 19th Century German philosopher who made a name for himself attacking Christianity and other cherished ideals of his age. The novel analyzes the impact of his feminine upbringing. His father died when he was five and he was brought up by pious women.